Continuous-wave measurement of the 1S Lamb shift in atomic hydrogen. - Beausoleil, R; McIntyre, D; Foot, C; Hildum, E; Couillaud, B; Hänsch, T (1987)
We have determined the 1S Lamb shift in atomic hydrogen with a precision of 2 parts in 104 by measuring the frequency of the 1S-2S transition observed by continuous-wave Doppler-free two-photon spectroscopy. We employ an interferometrically calibrated absorption line in Te2130 as our reference and obtain a 1S-2S interval of 2 466 061 413.8(1.5) MHz. Choosing a value of the Rydberg constant measured independently by high-resolution spectroscopy of the hydrogen Balmer- transition, we find the 1S Lamb shift to be 8173.3(1.7) MHz, in good agreement with the theoretical value of 8172.94(9) MHz. © 1987 The American Physical Society.